Moral Foundations of Forgiving in the Workplace. Issue 1 (1st January 2017) - Paul, Gregory D.; Putnam, Linda L.
Abstract : Offensive behavior can create problems in the workplace. How victims cope with such behavior creates a range of individual, relational, and organizational consequences. Coping practices such as avoidance and forgiveness are products of individual characteristics and organizational values and norms. The purpose of this study was to explore the association between coping practices and conflict-related values, norms, and practices across four organizations. The results point to a need to examine how emotion management, coping practices, and organizational values and expectations are interrelated.